Конфликт в польском экологическом дискурсе: попытка конверсационного анализа - Ранцев-Сикора, Д. (Социология: теория, методы, маркетинг, 2005)
In this article the author tries to explain a nature of conflict within the Polish ecological
discourse. The major four groups of amateurs and professionals were the subject of
consideration: professional ecologists, the participants of environmental social move
ment, forest rangers and licensed hunters. The author analyzes selected publications
from 8 journals for the years 1992–2001. The main problems analyzed were such:
group identities, conversational styles — conflict behavior. The research resulted in a
description of group cultures, which are characteristics of different cultural systems:
feudalism (hunters), Enlighenment (professional ecologists), industrialism (forest
rangers) and postindustrialism (environmental social movement). The conclusion
was that cultural differences between discourse participants are essential thus effective communication between them seems doubtful.